Effect of Light Quality, Light Intensity, and Cell Inoculum Arrangement on Growth, Pigment and Carbon Content from Spirulina platensis using LED Light - Dianursanti; Chempaka, Rayi Mishellia; Hartono, Nelvina; Habibah, Lulu; Praharyawan, Swastika (Bogor Agricultural University, Indonesia, 2025)
This study evaluates the effect of lighting and cell inoculum in Spirulina platensis cultivation on its growth, pigment composition, and ability to capture CO2. Different light intensities (1,000, 3,000, and 5,000 lux), light quality (white, blue, and red), and cell inoculum which are shown as OD values (0.2, 0.3, and 0.5) were assessed. The highest growth rate was obtained from red light, followed by white and blue light. The maximum biomass concentration (0.0711 mg/ml) was obtained when red light was used under 5,000 lux light intensity. The highest carbon content (5.1274 mg/ml algae) was also obtained during red light cultivation under 5,000 lux light intensity. Meanwhile, the highest chlorophyll (1.4365 mg/mg algae) content was obtained at blue light cultivation under 5,000 lux intensity and OD 0.5 cell inoculum. The highest phycocyanin (0.0309 mg/mg algae) was obtained under red light with 3,000 lux light intensity and OD 0.5 cell inoculum. It was found that the cultivation conditions to achieve high biomass and high pigment concentration were different.